Association Between Atrial Fibrillation and Cognitive Impairment in Individuals With Prior Stroke: A Meta-Analysis and Meta-Regression Analysis. Issue 6 (June 2020) - Kokkinidis, Damianos G.; Zareifopoulos, Nikos; Theochari, Christina A.; Arfaras-Melainis, Angelos; Papanastasiou, Christos A.; Uppal, Dipan; Giannakoulas, George; Kalogeropoulos, Andreas P.; Fontes, Joao Daniel T.
Abstract : Background and Purpose—: Atrial fibrillation (AF) is the most common chronic arrhythmia. Dementia and cognitive impairment (CI) are major burdens to public health. The prevalence of all 3 entities is projected to increase due to population aging. Previous reports have linked AF with a higher risk of CI and dementia in patients without prior stroke. Stroke is known to increase the risk for dementia and CI. It is unclear if AF in patients with history of stroke can further increase the risk for dementia or CI. Our purpose was to evaluate the impact of AF on risk for dementia or CI among patients with history of stroke. Methods—: Preferred Reporting Items for Systematic reviews and Meta-Analyses guidelines were followed. Pubmed, Scopus, and Cochrane central were searched. The outcomes of interest were dementia, CI, and the composite end point of dementia or CI. A random-effect model meta-analysis was performed. Meta-regression analysis was also performed. Publication bias was assessed with the Egger test and with funnel plots. Results—: Fourteen studies and 14 360 patients (1363 with AF) were included in the meta-analysis. In the meta-analysis of adjusted odds ratio, AF was associated with increased risk of CI (odds ratio, 1.60 [95% CI, 1.20–2.14]), dementia (odds ratio, 3.11 [95% CI, 2.05–4.73]), and the composite end point of CI or dementia (odds ratio, 2.26 [95% CI, 1.61–3.19]). The heterogeneity for the composite end point of dementia or CI was moderate (adjusted analysis). The heterogeneity for the analysis of the end point of CI only was substantial in the unadjusted analysis and moderate in the adjusted analysis. The heterogeneity for the end point of dementia only was moderate in the unadjusted analysis and zero in the adjusted analysis. Conclusions—: Our results indicate that an association between AF and CI or dementia is patients with prior strokes is possible given the persistent positive associations we noticed in the unadjusted and adjusted analyses. The heterogeneity levels limit the certainty of our findings. Abstract : Supplemental Digital Content is available in the text.